KEDUDUKAN VISUM ET REPERTUM DALAM PERTIMBANGAN HUKUM HAKIM TERHADAP PERKARA PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN - Aulia Nur Ainun; Arsyad Aldyan (Sebelas Maret University, 2023)
The purpose of this legal research is to determine the position of visum et repertum in the judge's legal considerations of persecution that caused death with the case study of Decision number 410/Pid.B/2020/PN.CKR. This legal research is included in the type of normative legal research which is prescriptive with a case approach and statutory approach. The data collection technique used by the authors in this legal research is a library research. The results of the reseacrh showed that the letter evidence is in the form of visum et repertum in the case with decision Nnmber 410/Pid.B/2020/PN CKR has an important role in assisting the Panel of Judges in their considerations for imposing a sentence on the crime ofpersecution that causing someone’s death which based on Article 183 of the Criminal Procedure Code, visum et repertum is required in strengthening other evidences that have existed. The position of the visum et repertum in the perspective of evidentiary law as a judge's legal considerations, it is an authentic deed that becomes valid evidence in accordance with the provisions of evidence set forth in Article 187 jo. Article 184 paragraph (1) letter c which plays a role in creating a material truth.Keywords: Visum et Repertum; Judge’s Legal Consideration; Persecution that Caused Death